RANCANG BANGUN RUANG STERILLISASI, PEMBACA SUHU TUBUH MENGGUNAKAN SENSOR MLX90614 BERBASIS ARDUINO - Yogi Pratama; Yussa Ananda (Universitas Harapan Medan, 2021)
Corona virus disease 2019 which is abbreviated as Covid-19 is a new type of corona outbreak that was discovered in Wuhan, Hubei, China in 2019. Covid-19 is the cause of respiratory tract infections. This tool is useful for minimizing the spread of Covid-19 with an Arduino Uno-based antiseptic misting automatic control system. This research was carried out in the integrated laboratory of Electrical Engineering Education, Harapan University, Medan. The arduino uno based automatic antiseptic misting control system is a system built on the Dettol antiseptic liquid antiseptic spraying device. This Arduino uno-based antiseptic misting can work according to a system designed to spray Dettol antiseptic liquid antiseptic for the human body, the way it works is when an object is at a predetermined point or distance, the PIR sensor will detect it and will send a signal to the Arduino uno. and then it will be processed to an actuator/pump which will drain the liquid to a 0.2 mm misting nozzle as a fluid channel that is positioned to provide turbulence to the fluid in this case the Dettol antiseptic liquid comes out through the apparatus as antiseptic dew for 7 seconds, how to identify covid-19 there are several ways One way to identify is by measuring body temperature. With the non-contact MLX90614 sensor, direct your hand towards the sensor without touching it. If the MLX 90614 sensor detects an object, the LCD will display the body temperature. The MLX90614 sensor reader then detects whether the body temperature is too high or too low, if the temperature is < 37℃ then the LCD will display